Engineering properties of stabilized tropical peat soils - Deboucha, S.; Hashim, Roslan; Alwi, A. (2008)
Peaty soils are not suitable as foundation soils as they are weak and highly compressible. This paper describes a study on peat soil stabilisation to improve its physical and engineering properties. It investigates the effect of additives (binder amount 5, 10 and 15 (85cement, 15 bentonite) and range of sand 5 to 25 on the index properties as well as, pH, compaction, California Bearing Ratio and unconfined compressive strength of tropical peat soils. The amount of additives added to the peat soil sample was investigated in terms of the percentage of the dry soil mass. The results showed that of the additive admixtures altered the engineering properties of tropical peat soils. The soil liquid limit was found to decrease with increase of the additive content. The pH was found to increase with increase binder. The maximum dry density was found to increase while the optimum moisture content was found to decrease with the increase of the additive content. The California Bearing Ratio of the soil was found to increase significantly with increase in the additives.